2010
DOI: 10.1007/s10528-010-9331-6
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Nutrigenetics on the Lipid Profile: Interaction Between Genes and Dietary Habits

Abstract: Nutrigenetics is a new field with few studies in Latin America. Our aim is to investigate the way in which different genes related to the lipid profile influence the response to specific dietary habits. Eight polymorphisms on seven genes were investigated in a sample (n = 567) from Porto Alegre, RS, Brazil. All the volunteers completed a food diary that was then assessed and classified into nine food groups. A number of nutrigenetic interactions were detected primarily related to the apolipoprotein E (apoE) ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 34 publications
0
14
0
1
Order By: Relevance
“…The absence of this gene SNP-dietary pattern interaction in men suggests that a combined set of polygenic variants may be relevant to this condition [6]; the difference in sex hormones and fat metabolism may be related to the rate of gene transcription, but the reasons for this are not well understood [36,37]. …”
Section: Discussionmentioning
confidence: 99%
“…The absence of this gene SNP-dietary pattern interaction in men suggests that a combined set of polygenic variants may be relevant to this condition [6]; the difference in sex hormones and fat metabolism may be related to the rate of gene transcription, but the reasons for this are not well understood [36,37]. …”
Section: Discussionmentioning
confidence: 99%
“…Saito et al reported similar results in patients with type 2 diabetes after a 14 day reduced fat diet therapy, showing a mean reduction of 15.6% for LDL-cholesterol and of 16.3% for total cholesterol in the ApoE3/4 group compared to 0.7 and 6.6%, respectively in the ApoE3/3 group (Saito et al, 2004). Variation in HDL-cholesterol following a diet rich in polyunsaturated fat is unclear (Masson et al, 2003; De Andrade et al, 2010); however, physical activity, particularly in ApoE4 carriers (Bernstein et al, 2002), increases HDL cholesterol (Marrugat et al, 1996; Kokkinos and Fernhall, 1999). These findings are encouraging because they suggest that alternative and/or complementary approaches can be use to control metabolic variation in ApoE4 carriers.…”
Section: Treatmentmentioning
confidence: 99%
“…Some studies have reported that diet may influence the effect of APOE polymorphism on blood lipid levels [13][15]. The data indicated that carriers of the ε4 allele were more responsive to high fat and cholesterol intake than those without the ε4 allele.…”
Section: Introductionmentioning
confidence: 99%